Superpredation patterns in four large Eupropean raptors - Lourenço, Rui (2012)
Predatory interactions among top predators, like superpredation or intraguild predation (IGP), can influence community structure. Diurnal raptors occupy high trophic levels in terrestrial food webs, and thus can regulate the presence of mesopredators. We studied superpredation (the killing and eating of another predator)in four large European raptors. We gathered 121 dietary studies, totalling 161,456 prey for the Goshawk Accipiter gentilis L., Golden Eagle Aquila chrysaetos L., Bonelli’s Eagle Aquila fasciata Vieillot, and Eagle Owl Bubo bubo L. Results showed that superpredation: (1) is a widespread interaction in large raptors, but it can vary according to the top predator species; (2) is not an important energetic resource for large raptors, but rather seems mostly related to diet diversification when the main prey decreases; (3) is spatially clustered reflecting habitat heterogeneity, but shows no temporal or large-scale spatial trends; and (4) it is associated with lower breeding success of the top predator species. These findings support the food stress hypothesis as the main driving force behind increases in superpredation and IGP in raptors, with the decrease in breeding performance as a side effect. Superpredation by large raptors deserves future research to understand its effects on mesopredators, because on one hand it might contribute to promote biodiversity, while on the other hand, it can sometimes represent an additional risk for small populations of endangered mesopredators.